Predicting North American Scolytinae invasions in the Southern Hemisphere - Lantschner, Maria Victoria; Atkinson, Thomas H.; Corley, Juan Carlos; Liebhold, Andrew M. (2017)
Scolytinae species are recognized as one of the most important tree mortality agents in coniferous forests worldwide, and many are known invaders because they are easily transported in wood products. Nonnative trees planted in novel habitats often exhibit exceptional growth, in part because they escape herbivore (such as Scolytinae) pressure from their native range. Increasing accidental introductions of forest pest species as a consequence of international trade, however, is expected to diminish enemy release of nonnative forest trees. In this context, there is need to characterize patterns of forest herbivore species invasion risks at global scales. In this study, we analyze the establishment potential of 64 North American Scolytinae species in the Southern Hemisphere. We use climate-based ecological niche models (MaxEnt) to spatially define the potential distribution of these Scolytinae species in regions of the Southern Hemisphere were pines are planted. Our model predicts that all of the pine-growing regions of the Southern Hemisphere are capable of supporting some species of North American Scolytinae, but there are certain “hotspot” regions, southeastern Argentina, Bolivia, Chile, Peru and southwestern Australia, that appear to be suitable for a particularly large number of species. The species with the highest predicted risk of establishment were Dendroctonus valens, Xyleborus intrusus, Hylastes tenuis, Ips grandicollis, Gnathotrichus sulcatus, and Ips calligraphus. Given that global commerce is anticipated to continue to increase, we can expect that more Scolytinae species will continue to establish outside their range. Our results provide information useful for identifying a global list of potential invasive species in pine plantations, and may assist in the design of comprehensive strategies aimed at reducing pest establishment in Southern Hemisphere forest plantations